2014
DOI: 10.1590/s1806-66902014000300025
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de feijão crioulo produzidas no oeste e planalto catarinense

Abstract: -This work was carried out with the aim of characterising landrace genotypes of the common bean as to the physiological potential of seeds produced in two consecutive seasons in different regions of the state of Santa Catarina, Brazil. The seeds of 26 genotypes were used, produced during 2009/2010 and 2010/2011 in the towns of Anchieta, Joaçaba and Lages. After the procedure for obtaining both mean and work samples, the following tests were carried out: first and second germination count, electrical conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
4
14
0
4
Order By: Relevance
“…Despite these differences, all the seeds presented germination rates above 80%, the minimum percentage required for the production and marketing of bean seeds (MAPA, 2013). Another aspect to highlight from the results obtained in the germination test is with reference to genetic variability among cultivars and the influence of the cultivation environment, indicating that some cultivars interact more favorably with the environment than others, enabling the production of higher quality seeds (MICHELS et al, 2014). The difference between the bean cultivars and their responses to the environments for the physiological quality of seeds has also been observed in studies conducted with cowpea (DUTRA et al, 2007) and creole beans (COELHO et al, 2010).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite these differences, all the seeds presented germination rates above 80%, the minimum percentage required for the production and marketing of bean seeds (MAPA, 2013). Another aspect to highlight from the results obtained in the germination test is with reference to genetic variability among cultivars and the influence of the cultivation environment, indicating that some cultivars interact more favorably with the environment than others, enabling the production of higher quality seeds (MICHELS et al, 2014). The difference between the bean cultivars and their responses to the environments for the physiological quality of seeds has also been observed in studies conducted with cowpea (DUTRA et al, 2007) and creole beans (COELHO et al, 2010).…”
Section: Resultsmentioning
confidence: 84%
“…When comparing the growing seasons, the highest emergence was observed for the dry season only for the cultivar 'IAC Carioca Precoce'. Michels et al (2014) reported differences in the emergence of creole bean under field conditions, between different sites of cultivation and claim that these results may be related to the weather conditions at the time of sowing. However, they found 1 Means followed by the same letters inside each dose of phosphorus do not differ at 0.05 probability level by Tukey test.…”
Section: Resultsmentioning
confidence: 99%
“…Contudo, estima-se que aproximadamente 89% dos produtores brasileiros de feijão utilizam grãos próprios para a semeadura (MICHELS et al, 2014;SILVA, 2015), tornando os plantios mais susceptíveis as condições adversas.…”
Section: Qualidade De Sementes De Phaseolus Vulgaris L No Contexto Dunclassified
“…Alguns trabalhos com sementes de feijoeiro têm sido realizados visando a avaliação da qualidade fisiológica (CASSOL et al, 2012;SILVA et al, 2014;MICHELS et al, 2014;PARREIRA et al, 2015;ZUCARELI et al, 2015 ), sanitária (ALMEIDA et al, 2013;BRITO et al, 2013); e física (MOTA, 2016). No entanto, poucas informações estão disponíveis sobre avaliações simultâneas entre sementes certificadas e não certificadas, para os diferentes aspectos que abrangem sementes de alta qualidade.…”
Section: Qualidade De Sementes De Phaseolus Vulgaris L No Contexto Dunclassified
“…Assim, o uso de sementes crioulas tem suas vantagens, por serem genótipos mais rústicose adaptadosa ambientes mais variados,e também por apresentaremresistência adoenças e pragas, especialmente as de ocorrência em seu local de cultivo (COELHO et al 2010;MICHELS et al 2014). …”
Section: Introductionunclassified